2010
DOI: 10.1166/jnn.2010.1964
|View full text |Cite
|
Sign up to set email alerts
|

Splitting and Flattening of Helical Carbon Nanofibers by Acid Treatment

Abstract: Helical carbon nanofibers (HCNFs), such as the carbon nanocoil (CNC) and the carbon nanotwist (CNTw), were synthesized by catalytic chemical vapor deposition using a substrate. HCNFs are classified into round and angular types according to the fiber cross-sections. When four types of HCNFs (round-type CNC and CNTw, angular-type CNC and CNTw) were acidified in a 30% hydrogen peroxide solution, only the angular type CNC was found to show a drastic shape change. The shape change observed was a splitting followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…It is well known that the catalyst composition plays a critical role in determining CNC morphology [19,20,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the catalyst composition plays a critical role in determining CNC morphology [19,20,22,23].…”
Section: Resultsmentioning
confidence: 99%
“…The weight loss and shape change of CNCs by acid treatment for 1 h were evaluated. (Yokota et al, 2010) The weight decreased as the temperature was increased. Furthermore, the weight decreased dramatically at 80-120ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Syntheses and Electronic Applications of Helical Carbon Nanofibres 41 alloys (Fe-Cr-Mn-Mo, Fe-Cr-Ni-Mo (SUS513), Fe-Ni-Cr-Mo-Mn-Sn) (Yang et al, 2004), (Yang et al, 2005), Ni/SnO 2 (Hosokawa et al, 2007), Ni/Sn (Yokota et al, 2010), Cu-(Ni, Cr, Ti or Zn) (Takikawa et al, 2000), and Ni/Cu . According to our experimental results, it is possible to grow CNC and CNTw selectively by the combination of binary catalyst; CNC is synthesized by Fe-based catalyst, and CNTw synthesized by Ni-based catalyst.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…The low CNC purity is ascribed to the thickness of the carbon layer. Yokota et al [45] reported that the thickness of the carbon layer depends on the thickness of the catalyst film on the substrate.…”
Section: Catalystmentioning
confidence: 99%
“…We used a drop-coating method to deposit catalyst films on substrates, as reported in our previous study [44,45]. Although this method is convenient, the catalyst films tended to be thick under our experimental conditions.…”
Section: Catalyst Formationmentioning
confidence: 99%